Kepuasan Memediasi Pengaruh Layanan AI, SMM, Keunggulan Produk terhadap Loyalitas Pelanggan Bank Umum Syariah - Kholishoh, Ziadatun; Bahjatulloh, Qi Mangku (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
The purpose of this study was to determine how strong the influence of artificial intelligence-based services, social media marketing, and product excellence on customer loyalty of Islamic Banks in East Java with customer satisfaction as an intervening variable. This study uses a quantitative approach with data collection techniques using a questionnaire with an interval scale of 1-5 to customers of Islamic Banks and domiciled in East Java. The sample taken was 400 respondents with a nonprobability sampling technique. This study uses the Partial Least Square (PLS) instrument approach to process data because it is one of the alternative Structural Equation Modeling (SEM) techniques that are often used to analyze the correlation between several complex variables. This study found that artificial intelligence-based services have a significant positive effect on customer loyalty and satisfaction of Islamic Banks. Social media marketing has a significant positive effect on customer loyalty and satisfaction of Islamic Banks. The product excellence variable does not have a significant effect on customer loyalty of Islamic Banks, but has a significant positive effect on customer satisfaction of Islamic Banks. The researcher also added an Intervening variable to mediate the three independent variables. The result is that the customer satisfaction variable is able to mediate the three variables.